Comparative analysis of distinct phenotyping methods for assessing wheat resistance and pathogen virulence among Fusarium species causing head blight disease - Vahideh Rafiei; Liza DeGenring; Erin M. Schwister; James Mitch Elmore; Mukesh Dubey; Magnus Karlsson; Milton T. Drott (Plant Methods)
Abstract Developing disease-resistant crops is a critical strategy for reducing chemical treatments and mitigating plant disease outbreaks, particularly amid global environmental changes. Fusarium head blight (FHB), caused by a complex of Fusarium species, is one of the most devastating cereal diseases, leading to significant economic losses and contamination of grain with harmful mycotoxins that threaten global cereal production and human health. The high variability in virulence within the complex of Fusarium spp and the lack of efficient high-throughput screening methods have impeded the development of resistant cultivars and made large-scale virulence testing labor-intensive and time-consuming. This study evaluates the efficacy of detached leaf, coleoptile, and seedling assays as high-throughput alternatives to the standard head infection assay for assessing the virulence of Fusarium species and differentiating wheat genotypes by resistance or susceptibility. Two near-isogenic wheat lines, one carrying FHB resistance loci and the other without, were used to assess the virulence of four Fusarium species. The seedling and coleoptile assays showed strong concordance with the traditional head infection assay, accurately reflecting differences in disease severity across Fusarium species and between wheat lines. Conversely, the detached leaf assay provided some differentiation among species but was inconsistent in identifying differences between plant genotypes. Across all assays, F. graminearum consistently exhibited the highest virulence, causing severe disease in leaves, stems, seedlings, and heads, while F. poae was the least virulent. Interestingly, F. culmorum and F. avenaceum displayed tissue-specific variability. These findings establish the coleoptile and seedling assays as rapid, high-throughput alternatives for breeding programs, accelerating the identification of FHB-resistant genotypes and reducing the reliance on the labor-intensive head assay.